2016
DOI: 10.1093/brain/aww287
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted prediction errors index social deficits in autism spectrum disorder

Abstract: In healthy individuals the anterior cingulate gyrus signals social prediction errors: discrepancies between an actual outcome and the perceived expectations of another person. Balsters et al. demonstrate that this crucial social signal is altered in individuals with autism, and that variability in social prediction error signalling indexes social symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 67 publications
3
77
1
Order By: Relevance
“…More specifically, studies examining neural responses to others’ rewards have demonstrated hypoactivation in the ACC, a region shown to be involved in processing social information more broadly as well as reward-related information for other individuals (Balsters et al 2017; De Martino et al 2008; Lockwood 2016; Lockwood et al 2015). Further, given that predicting reward outcomes also depends on probability, atypical effort expenditure for vicarious rewards may arise due to atypical computation of socially-specific prediction errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, studies examining neural responses to others’ rewards have demonstrated hypoactivation in the ACC, a region shown to be involved in processing social information more broadly as well as reward-related information for other individuals (Balsters et al 2017; De Martino et al 2008; Lockwood 2016; Lockwood et al 2015). Further, given that predicting reward outcomes also depends on probability, atypical effort expenditure for vicarious rewards may arise due to atypical computation of socially-specific prediction errors.…”
Section: Discussionmentioning
confidence: 99%
“…A common trait of individuals with ASD is intolerance of uncertainty or unpredictability, particularly in social contexts, which may reflect underlying impairment in predictive abilities (Sinha et al 2014). Notably, aberrant neural responses to social prediction errors have been observed in individuals with ASD relative to controls (Balsters et al 2017). Therefore, unexpected rewards in the context of others may be processed differently in individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of decision-making, it was found that the ventromedial prefrontal cortex encodes both probabilities about social and nonsocial sources, appearing to integrate information from ACC sulcus and ACC gyrus in a subject-specific fashion. Consequently, the above-mentioned brain regions could potentially play an important role in the investigation of ASC-related differences in multimodal cue integration and contextualization of precision in social and nonsocial cues [90,91]. …”
Section: Individual Level: Predictive Processing and Active Inferencementioning
confidence: 99%
“…This suggests that the response of ACCg to rewards that others will receive may depend on their group membership. Moreover, the connections between the ACCg and the VMPFC (Apps et al., 2016; Balsters, Mantini, Apps, Eickhoff, & Wenderoth, 2016; Vogt, 2009) and the fact that both regions showed a profile indicative of signaling information in an ingroup centered reference frame suggests that they may form part of a network that plays an important role when interacting in social groups (Balsters et al., 2017; Sallet et al., 2011). …”
Section: Discussionmentioning
confidence: 99%